(untitled) (Revista Brasileira Multidisciplinar, 2023)
The Strategic Options Development Analysis – SODA is a tool to structure complex problems that uses the cognitive mapping technique to support strategy formulation processes. The objective of this study was to identify, describe and analyze scientific articles which have used the SODA method and/or the cognitive mapping (CM) technique in Brazil. A bibliographic review was carried out on the Google Scholar and Scielo bases, as well as in the database records of the following events: SIMPEP (Symposium of Production Engineering), CONBREPRO (Brazilian Congress of Production Engineering) and ENEGEP (National Meeting of Production Engineering). The results allowed us to verify an increase in the interest in the subject since 2015, as well as its large application in government and public services. The study also showed that SODA can be combined with other methods/tools and that only few studies have used software support to build cognitive maps. From these research results, it was possible to conclude that SODA and CM proved to be effective for structuring problems in several areas.